A survey of voice and communication protection solutions against wiretapping. (July 2019) - Ntantogian, Christoforos; Veroni, Eleni; Karopoulos, Georgios; Xenakis, Christos
Abstract: This paper categorizes, presents and evaluates a set of schemes and solutions that provide end-to-end encryption for voice communications. First, we analyze the research works that propose new schemes that enable the transfer of encrypted speech over the voice channel of the 2nd generation mobile network. Next, we analyze a set of popular widespread software applications that use Voice over IP technology to provide secure communications, and finally, we investigate commercial solutions, which are hardware-based and offer voice encryption for both 2nd generation and Voice over IP communications. After the presentation of the existing solutions, we evaluate them based on the following criteria: (i) security level provided, (ii) possible performance issues and (iii) usability. We conclude this work by providing future research directions. To the best of our knowledge, this is the first paper that categorizes and provides a comprehensive evaluation of end-to-end voice encryption schemes for mobile networks.